PERANCANGAN DESIGN E-COMMERCE PADA CV.GREANTEA SHOP DENGAN PENDEKATAN USER CENTERED DESIGN (UCD) - Miradz, Arik; Wijaya, Hendra; Choirunisa, Syifa; Yoraeni, Ani (Jurnal Teknologi Sistem Informasi, 2022)
CV. Greanteashop Mozayoo Group is a business engaged in the distribution of frozen food.CV. Geanteashop Mozayoo Group also plans to create a website for customers so that people can shop without fear of contracting the Covid-19 disease and don't have to bother coming to the store. This study aims to optimize the website by utilizing the UCD method. SUS is a method of calculating tools to measure the usability of the created website or success. Testing the sales website on CV. Greentea Shop uses a usage system scale with 10 questions. The User Experience Questionnaire method itself has 26 questions. The results of collection techniques from observations and interviews from data collection results from user or user needs, namely the display must be as attractive as possible for the convenience of the user or user, the display must have images so that users do not feel bored, the system must be easy to understand. The results of the test using SUS obtained an average score of 86, where the score has a result of 86 percent and is graded A based on the SUS score. aspects obtained: 1.98 attractiveness, 1.08 clarity, 2.08 efficiency, 1.79 accuracy, 2.19 stimulation. and novelty 1.88. All aspects get a positive score.